Early Stimulation in Learning Activation on Early Childhood - Lucia Vinueza Reina, Ana; Vegas Melendez, Hilarion (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this scientific research is to describe the importance of the early stimulation process in the activation of the learning of children in initial education; as well as highlighting the difficulties that exist, the methodological guidelines applied, the pedagogical resources used, the participation of parents/family and other variants related to the subject. To achieve these purposes, it was necessary to apply a qualitative-quantitative study, guided by the inductive, deductive, descriptive, analytical-synthetic, statistical, descriptive and bibliographic methods to determine, verify and understand the processes involved in early education. The results achieved show that early stimulation is a timely training process, where children develop skills and begin the activation of learning, being feasible to apply strategies through a set of techniques, recreational activities and teaching resources that facilitate integral development Education is the responsibility of teachers and parents who must stimulate children in order to contribute to the construction of knowledge to enhance initial training, this being the main axis, which guarantees the development of the potential and intelligence of infants during the first years of life in interactive environments.